2016
DOI: 10.1093/nar/gkw175
|View full text |Cite
|
Sign up to set email alerts
|

PolDIP2 interacts with human PrimPol and enhances its DNA polymerase activities

Abstract: Translesion synthesis (TLS) employs specialized DNA polymerases to bypass replication fork stalling lesions. PrimPol was recently identified as a TLS primase and polymerase involved in DNA damage tolerance. Here, we identify a novel PrimPol binding partner, PolDIP2, and describe how it regulates PrimPol's enzymatic activities. PolDIP2 stimulates the polymerase activity of PrimPol, enhancing both its capacity to bind DNA and the processivity of the catalytic domain. In addition, PolDIP2 stimulates both the effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
94
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(102 citation statements)
references
References 32 publications
(109 reference statements)
8
94
0
Order By: Relevance
“…Poldip2 is fairly ubiquitously expressed, having been reported in aorta, 3, 4 lung, 3 kidney, 3, 5, 6 heart 7 and thyroid, 8 as well as many cell types including mouse aortic smooth muscle cells, 9 astrocytes, 10 vascular smooth muscle cells (VSMC), 3, 11 brain endothelial cells, 12 epithelial cells, 12 HeLa, 1, 12-15 fibroblasts, 2, 13, 16, 17 kidney fibroblasts, 18 myoblasts, 19 human umbilical vein endothelial cells, 20 human embryonic kidney cells 293 (HEK 293), 13 MRC5 cells, 21, 22 and cortical neurons. 23 There is also evidence of Poldip2 expression in human breast cancer, 24 human breast adenocarcinoma cells 13 and human lung adenocarcinoma cells.…”
Section: Tissue Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Poldip2 is fairly ubiquitously expressed, having been reported in aorta, 3, 4 lung, 3 kidney, 3, 5, 6 heart 7 and thyroid, 8 as well as many cell types including mouse aortic smooth muscle cells, 9 astrocytes, 10 vascular smooth muscle cells (VSMC), 3, 11 brain endothelial cells, 12 epithelial cells, 12 HeLa, 1, 12-15 fibroblasts, 2, 13, 16, 17 kidney fibroblasts, 18 myoblasts, 19 human umbilical vein endothelial cells, 20 human embryonic kidney cells 293 (HEK 293), 13 MRC5 cells, 21, 22 and cortical neurons. 23 There is also evidence of Poldip2 expression in human breast cancer, 24 human breast adenocarcinoma cells 13 and human lung adenocarcinoma cells.…”
Section: Tissue Expressionmentioning
confidence: 99%
“…In addition, Poldip2 stimulates the efficiency and error-free 8-oxo-7,8-dihydroguanine (8-oxo-G)DNA lesion bypass by PrimPol. 21 However, another study suggested that Poldip2 does not directly participate in the process of TLS, because it is not recruited to sites of DNA damage upon UV stimulation. Instead, Poldip2 translocates to spliceosomes and contributes to UV-induced MDM2 alternative splicing.…”
Section: Functions Of Poldip2mentioning
confidence: 99%
“…A number of studies have shown that PrimPol is important for the maintenance of replication after damage and loss of the protein causes UV-C sensitivity, slowing of replication and cell cycle arrest in avian DT40 cells (10,12,15,19). PrimPol has been shown to interact with a number of replicationassociated proteins, such as RPA and PolDIP2, which are likely to be important for its recruitment and function at sites of stalled replication (20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…An earlier study showed that human PolDIP2 increases the DNA polymerase activity of PrimPol (22). The crosslinking experiments in that study identified several regions as potential PrimPol-PolDIP2 interaction sites: however, the mechanism behind the PolDIP2-dependent stimulation of PrimPol DNA synthesis remained unclear.…”
Section: The C-terminal Region Of Poldip2 Increases the Processivity mentioning
confidence: 97%